The Effect of Tourist Attractiveness Based on the 4A Concept on Tourists’ Interest in Visiting Peucang Island, Ujung Kulon - Florencea Irena; Lamtiar Hema Malini (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Pulau Peucang, located within Ujung Kulon National Park, is a nature-based tourism destination with tourism attraction potential based on the 4A concept, namely attraction, accessibility, amenities, and ancillary services. This study aims to analyze the effect of 4A-based tourism attraction dimensions on tourists’ intention to visit Pulau Peucang, Ujung Kulon. This study employed a quantitative approach using a survey method. Data were collected from 106 respondents consisting of tourists who had visited or were currently visiting Pulau Peucang and were selected using accidental sampling. Data were analyzed using multiple linear regression with IBM SPSS Statistics version 27. Before hypothesis testing, classical assumption tests were conducted, including normality, multicollinearity, and heteroscedasticity tests. The findings indicate that, simultaneously, attraction, accessibility, amenities, and ancillary services do not have a significant effect on tourists’ visit intention (p = 0.165). Partially, attraction, accessibility, and amenities do not significantly influence visit intention, whereas ancillary services have a significant effect (p = 0.043). The coefficient of determination (R² = 0.062) shows that the model explains only 6.2% of the variance in visit intention, while 93.8% is influenced by factors outside the model. This study concludes that, among the four dimensions of the 4A concept, only ancillary services significantly influence tourists’ intention to visit Pulau Peucang. The findings contribute to nature-based tourism management by highlighting the strategic importance of supporting services and institutional facilities in strengthening tourists’ visit intention.